Generation of two hiPSC lines from a patient with autism spectrum disorder harboring a 120 kb deletion in SHANK2 and two control lines from each parent - Cristian, Flavia-Bianca; Köppel, Alexandra; Janssen, Johannes W. G.; Utikal, Jochen; Rappold, Gudrun; Berkel, Simone (Stem cell research, 2020)
Two human induced pluripotent stem cell lines (hiPSC) were generated by reprogramming fibroblasts isolated from a skin biopsy taken from a female patient diagnosed with autism spectrum disorder (ASD) and intellectual disability (ID). This patient harbors a de novo 120 kb deletion in SHANK2. As controls, four lines were generated in a similar manner from fibroblasts isolated from each of her parents, two clones per parent. All reported hiPSC lines have a normal karyotype, express pluripotency markers and have the ability to differentiate into all three germ layers.
Gesehen am 16.02.2021